Microbeam methodologies as powerful tools in manganese hyperaccumulation research: present status and future directions - Fernando, Denise R.; Marshall, Alan; Baker, Alan J.; Mizuno, Takafumi (Frontiers in Plant Science, 2013)
Microbeam studies over the past decade have garnered unique insight into manganese (Mn) homeostasis in plant species that hyperaccumulate this essential mineral micronutrient. Electron- and/or proton-probe methodologies employed to examine tissue elemental distributions have proven highly effective in illuminating excess foliar Mn disposal strategies, some apparently unique to Mn hyperaccumulating plants. When applied to samples prepared with minimal artefacts, these are powerful tools for extracting true ‘snapshot’ data of living systems. For a range of reasons, Mn hyperaccumulation is particularly suited to in vivo interrogation by this approach. Whilst microbeam investigation of metallophytes is well documented, certain methods originally intended for non-biological samples are now widely applied in biology. This review examines current knowledge about Mn hyperaccumulators with reference to microbeam methodologies, and discusses implications for future research into metal transporters.